PENGARUH TERAPI BEKAM TERHADAP PENURUNAN NYERI PADA PASIEN LOW BACK PAIN DI KLINIK ZEIN HOLISTIC MAKASSAR - Sitti Aminah; Samsualam; Eliati Paturungi; Yuliana (CV. Adiba Aisha Amira, 2025)
Low back pain can be treated through pharmacological and non-pharmacological therapies. One widely used non-pharmacological method is cupping therapy. Cupping therapy is a traditional healing method that has been known for thousands of years and is used in various parts of the world, including Indonesia. This therapy involves applying special cups to the skin's surface to create negative pressure. This process aims to increase blood flow, reduce muscle tension, and help remove toxins from the body. There are two types of cupping therapy: dry cupping and wet cupping. Objective: To determine the effect of cupping therapy on pain reduction in patient Mrs. R with low back pain at the Zein Holistic Clinic. Method: This is a case study describing the findings in one patient, Mrs. R, with a medical diagnosis of low back pain.Nursing Care Outcomes: The nursing diagnosis established based on Mrs. R's assessment was acute pain. Treatment for low back pain, including cupping therapy, was administered on August 11, 2025, at the Zein Holistic Clinic in Makassar. Based on the assessment results, the pain scale was 6/10 using the Numerical Rating Scale (NRS). After cupping therapy, the pain decreased to 4/10. The cupping points used, based on the Sunnah, were Azh-Zhar and Al-Warik. Conclusion: Cupping therapy is expected to reduce Mrs. R's pain. This is expected to provide input for ongoing topic development.